Attitudes and Practices of Pulmonary Tuberculosis Prevention among Family with Tuberculosis in Children Specialist Polyclinic, Center of Lung Health Makassar Community - Nur Azizah Azzahra; Giyantolin Giyantolin; Khairunisa; Nur Mila Sari; Rifka Haristantia; Alchamdani; Adhe Sofyan Anas (Innovative: Journal Of Social Science Research, 2024)
The trend in the proportion of children with tuberculosis or TB cases in Indonesia has increased from 2014 to 2016. Family attitudes and practices include factors related to the incidence of TB in children. This study aims to describe the attitudes and practices of TB families regarding the prevention of pulmonary TB in the Children's Specialist Polyclinic of the Makassar Center for Lung Health. The type of research used is quantitative with a descriptive approach. The sample was determined using a purposive sampling method so that 31 families of TB patients of children who were respondents to this study were obtained—data analysis using univariate analysis. The results showed that the attitude of respondents was more positive, with several 16 people (51.6%). In contrast, respondents who had a negative attitude were 15 people (48.4%). Respondent's practice is more in the good category, with 19 people (61.3%), and bad practices in as many as 12 people (38.7%). This study concludes that most respondents have good attitudes and practices regarding pulmonary tuberculosis. It is recommended that the relevant agencies put up posters, provide leaflets in the pediatrician's polyclinic waiting room, provide educational advertisements about pulmonary tuberculosis in the main waiting room, and provide routine counseling to the families of tuberculosis patients.